Producer Perceptions Toward Prevention and Control of Lameness in Dairy Cows in Alberta Canada: A Thematic Analysis - Knauss, Marlena; Adams, Cindy L.; Orsel, Karin (Frontiers in Veterinary Science, 2022)
Lameness in dairy cattle poses both an animal welfare and economic threat to dairy farms. Although the Canadian dairy industry has identified lameness as the most important health issue, lameness prevalence in the province of Alberta has not decreased over the last decade. Factors related to lameness have been reported, but the prevalence remains high. Therefore, this study was conducted to investigate dairy producers’ perceptions on lameness and how these perceptions influence lameness prevalence in their cows. Qualitative interviews with open-ended questions were conducted with nine dairy producers in Alberta, Canada presenting farms with a wide variety of lameness prevalence. Thematic analysis of these interviews revealed five major themes, as well as five distinct types of producers regarding their perceptions. All nine producers mentioned similar challenges with lameness prevention and control. Identifying lameness, taking action, delays in achieving success, various approaches to prevention and control strategies, and differences between farms were the challenges encountered. However, producers’ attitudes when dealing with these challenges varied. We concluded that understanding producers’ perceptions is essential when advising them regarding how to address lameness, as guidance and support will be most successful when it is aligned with their viewpoint.